Strokes in young adults: epidemiology and prevention - Smajlovic, Dzevdet (Vascular health and risk management, 2015)
Strokes in young adults are reported as being uncommon, comprising 10%-15% of all stroke patients. However, compared with stroke in older adults, stroke in the young has a disproportionately large economic impact by leaving victims disabled before their most productive years. Recent publications report an increased incidence of stroke in young adults. This is important given the fact that younger stroke patients have a clearly increased risk of death compared with the general population. The prevalence of standard modifiable vascular risk factors in young stroke patients is different from that in older patients. Modifiable risk factors for stroke, such as dyslipidemia, smoking, and hypertension, are highly prevalent in the young stroke population, with no significant difference in geographic, climatic, nutritional, lifestyle, or genetic diversity. The list of potential stroke etiologies among young adults is extensive. Strokes of undetermined and of other determined etiology are the most common types among young patients according to TOAST (Trial of Org 10172 in Acute Stroke Treatment) criteria. Prevention is the primary treatment strategy aimed at reducing morbidity and mortality related to stroke. Therefore, primary prevention is very important with regard to stroke in young adults, and aggressive treatment of risk factors for stroke, such as hypertension, smoking, and dyslipidemia, is essential. The best form of secondary stroke prevention is directed toward stroke etiology as well as treatment of additional risk factors. However, there is a lack of specific recommendations and guidelines for stroke management in young adults. In conclusion, strokes in young adults are a major public health problem and further research, with standardized methodology, is needed in order to give us more precise epidemiologic data. Given the increasing incidence of stroke in the young, there is an objective need for more research in order to reduce this burden.